PARADIPLOMACY PRACTICE IN INDONESIA: A LESSON FROM WEST NUSA TENGGARA PROVINCE IN 2013-2019 - Pratama, Dhany Putra (Universitas Muhammadiyah Yogyakarta, 2020)
This article attempts to reveal the factors inflicting the decision-making process of paradiplomacy in West Nusa Tenggara within the course of six years between 2013 and 2019 including the problems faced by them under the administration of two governors, Tuan Guru Bajang and Dr. Zulkieflimansyah. Utilizing rational choice theory in form of qualitative-descriptive research, various field findings and literatures indicate that external and internal factors consisting of combination of individual and bureaucratic rationalities and influence play significant roles in driving said trend. The policy, however, is not flawless as errors and issues related to inequality and lack of proper management become points of critics by many.